Exploring The Role of Assesment in Supporting Deep Learning in Mathematic: A Qualitatve Literature Study - Lubis, Putri Alawiyah; Kartini, Iin; Utari, Kania; Pohan, Lisa Rahmadani; Toruan, Sischa Monika Lumban (Universitas Muhammadiyah Surakarta, 2025)
This study aims to examine the role of assessment in supporting deep learning in mathematics through a qualitative literature review method. Data were obtained from a systematic search on Google Scholar, DOAJ, and the national education repository using the keywords 'deep learning' and 'mathematics assessment,' focusing on articles published since 2022 that are relevant to primary and secondary education in Indonesia. Ten articles met the inclusion criteria and were analysed thematically to identify patterns of strategies, outcomes, and the relationship between assessment and deep learning. The results of the study indicate that assessment plays a role not only in measuring final outcomes but also in monitoring thinking processes, conceptual understanding, and the ability to connect material to real-world contexts. The implementation of continuous formative assessment, projects, portfolios, and instruments based on Higher Order Thinking Skills (HOTS) has proven effective in promoting student engagement, providing constructive feedback, and strengthening 21st-century skills. The integration of authentic assessment with innovative learning models such as Indonesian Realistic Mathematics Education (PMRI), Problem-Based Learning, Project-Based Learning, and interactive evaluation technology enriches the learning experience and supports the achievement of the Pancasila learner profile. Challenges include limitations in teacher understanding, learning resources, and a tendency for assessment to focus on final outcomes. This study recommends teacher training, the development of practical guidelines, and further research to optimise the integration of assessment and deep learning in the context of mathematics education.